O Cerrado e as possibilidades didático pedagógicas nas aulas de geografia da educação básica - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The research addresses the urgent need to preserve the Cerrado biome, considering that the development model based on market expansion is a significant cause of adverse environmental impacts. In this context, the role of education in raising students' awareness of socio-environmental issues is recognized. The re-search problem focuses on how academic and school practices can contribute to understanding the natural, social, economic, cultural, political, and geopolitical aspects of the Cerrado, encouraging its appreciation and, consequently, its preservation through awareness and the adoption of sustainable attitudes. Thus, this study aims to enhance the teaching of the Cerrado in Geography at the elementary school level by reflect-ing on the purpose of Geography education, analyzing the presence of this theme in curricula and text-books, examining teaching practices, and developing didactic pathways. To this end, the study is based on documentary and bibliographic review, including an analysis of the Base Nacional Comum Curricular (BNCC) and the Diretrizes Curriculares do Estado de Goiás (DCGO), as well as a case study in a public school in Aragarças, Goiás. Teaching practices, curricular content, and students' perceptions of the biome were observed. The methodology, adopting a qualitative approach, included participant observation, semi-structured interviews, and document analysis. Finally, didactic pathways were proposed, based on ap-proaches, resources, and strategies that promote meaningful learning. The results highlight the need for greater emphasis on the Cerrado in school curricula, not only in terms of its physical aspects but also its cultural and socioeconomic dimensions. This issue is particularly relevant given that textbooks do not address the topic in sufficient depth. Through the proposed didactic sequences, this research aims to pro-vide tools for the formation of critical and aware citizens who recognize the importance of the Cerrado, reinforcing the school's role in building knowledge that values the biome and promotes its sustainability.
The Cerrado and the didactic pedagogical possibilities in geography classes of basic education
Keywords: Geografia escolar; Bioma; Preservação; Percurso didático; School geography; Biome; Preservation; Didactic pathway; CIENCIAS HUMANAS::GEOGRAFIA; CIENCIAS HUMANAS::EDUCACAO